FUNCTIONS OF THE PREPOSITION Z IN VASYL STEFANYK’S NOVELLAS - Lesiuk, Mykola (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
Mykola Lesiuk’s article «Functions of the preposition Z in Vasyl Stefanyk’s novellas» examines a fragment of the Language Dictionary of the fictional works of this outstanding Ukrainian novella author (Mykola Lesiuk. The Language Dictionary of Vasyl Stefanyk’s Fictional Works (a fragment). Ivano-Frankivsk : Misto NV. 2021. 384 p.), in particular the role of the preposition Z and its variants. The aim of the article – to show and illustrate how the dictionary entry on the functions of the preposition Z and its variants in V. Stefanyk’s fictional works is created, the richness of relations these or those words enter into thanks to this preposition. While creating the dictionary there were used the principles of compiling dictionaries of writers’ language, developed as far back as at the end of the previous century by Professor I. Kovalyk and somewhat renewed and perfected by the compiler of the Dictionary and the author of this article. The article traces how these principles are embodied in practice. The research methods lay in the exhaustive analysis of dictionary entries, the entry on the preposition Z in particular. The methods of creating the Dictionary foresaw the thorough examination of the writer’s texts in V. 1 of Vasyl Stefanyk’s academic edition(1949) and writing out word combinations with the preposition Z from them, establishing sense and grammar relations that appeared due to the preposition Z. The research results. Since the compilation of the dictionary of the writer’s language is too complicated and laborious work, meant for a group of people, there was created only a fragment of the dictionary consisting of seven letters, that, however, has a great practical significance because it can serve as the model for creating other similar dictionaries or a full dictionary of V. Stefanyk’s language, and the article on the preposition Z may serve as the pattern for describing functions of other prepositions or function words. The article’s scientific novelty does not arouse any doubt as in the Ukrainian linguistics there were no publications tracing the employment of the functional parts speech in works of a separate author.